SDM sebagai Determinan Pengukuran Efisiensi Puskesmas (Studi pada Puskesmas di Kabupaten Bantul, Yogyakarta) - Sri Widodo; ratna purnama sari (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2020)
The purpose of this research is to examine the efficiency level of non-inpatient public health centers (puskesmas) in Bantul Regency. A total of 11 puskesmas are used to be sample in this research. Efficiency is a comparison of inputs with outputs where input uses in this research are the number of human resources both health and non health staff, while the output uses in this research are the number of patient visits, the number of dengue cases and the number of diarrhea cases. Data is processed using Input-based Variable Return to Scale Data Envelopment Analysis (DEA) where the puskesmas can only control the amount of input. The DEA results show that only 4 puskesmas were declared efficient while the rest were not. The majority of puskesmas in Bantul Regency are considered inefficient in placing human resources so that it is excessive in terms of numbers serving patients and handling cases that occur.